Organizational Culture and Employee Engagement, Investigating the Role of Knowledge Sharing among Bank Employees - Indriyani, Ratih; Eliyana, Anis; Sobirin, Achmad; Agatha, Amelia (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge sharing is an important activity for organization to maintain their sustainability and maintaining their consumers. On the other hand, organizational culture can encourage knowledge sharing among employee and increase their working engagement. This research aims to examine the effect of organizational culture on employee engagement through knowledge sharing as an intervening variable. This research was conducted through survey at banking frontliner employees in Surabaya. The sample used was 100 employees using purposive sampling technique. Data analysis is conducted using Partial Least Square. The result of the study shows that organizational culture influences knowledge sharing. Knowledge sharing has a significant and positive influence toward employee engagement. The results also show that knowledge sharing has a significant and positive impact on employee involvement in work.